2021
DOI: 10.55275/jposna-2021-245
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Femur Guided Growth for the Management of Hip Dysplasia in Children with Cerebral Palsy

Abstract: Proximal femoral deformity associated with neuromuscular hip dysplasia in children with cerebral palsy (CP) is characterized by increased anteversion, coxa valga, and caput valgum.  Guided growth of the proximal femur (PFGG) utilizes a screw to tether the medial portion of the physis to achieve progressive varus alignment of the femoral head and neck with subsequent growth.  This procedure has been shown to decrease the head shaft angle and Reimer’s migration percentage (RMP); and decrease the need for subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Davids [35] has published a detailed technical summary of TMH-PF and has identified guided growths as a minimally invasive, safe and effective treatment options for CP patients with hip dysplasia. Most patients in the reported studies [32,34,47] were between 4 and 12 years of age and had a GMFCS of III-V; however, TMH-PF was performed in GMFCS I and II children by others [46].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Davids [35] has published a detailed technical summary of TMH-PF and has identified guided growths as a minimally invasive, safe and effective treatment options for CP patients with hip dysplasia. Most patients in the reported studies [32,34,47] were between 4 and 12 years of age and had a GMFCS of III-V; however, TMH-PF was performed in GMFCS I and II children by others [46].…”
Section: Discussionmentioning
confidence: 99%
“…This can justify extended hip surveillance into adulthood and surgical intervention in selected cases [55]. Apart from GMFCS, Davids recommends an MP of 25 to 50% and an age between 4 and 10 years as indications for this guided growth procedure, and it was hypothesized that early surgical treatment is associated with greater potential for improvement of hip valgus; however, the likelihood of screw revision surgery due to the physis growing off the screw (whereby the screw no longer crosses the physis) is also increased [35]. A recent publication from the Cerebral Palsy Integrated Pathway Scotland (CPIPS) database concluded that the 'point of no return' for hip subluxation in this population was a MP > 46%, making spontaneous improvement unlikely [56]; however, others advocated a lower threshold for surgical intervention [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations